LITERATURE REVIEW: THE IMPACT OF TECHNOPRENEURSHIP COMPANIES ON THE INCOME OF MECHANIZED RICKSHAW DRIVERS - Qori Fadla Ajmilia; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
This research examines the impact of the emergence of technopreneurship companies, such as Grab and Gojek, on the livelihoods of motorized pedicab drivers in the transportation sector. Using a literature review method, this research concludes that the increase in the use of online transportation services has caused a decrease in customers and income for motorized pedicab drivers. Suggested strategies to overcome this challenge include training and support for pedicab drivers to switch to online services, increasing digital skills, as well as collaboration between relevant stakeholders. Apart from that, pedicab drivers also adopt a strategy of restraint by not setting fixed rates. The wife's role can also be strengthened in supporting the continuity of family income. Further research and more sustainable strategies are needed to maintain the welfare of motorized pedicab drivers amidst technological changes in the transportation industry.